Tecendo saúde mental de adolescentes na atenção básica - Sousa, Leíza Melo (2024)
romoting comprehensive care for adolescents represents a challenge for health systems, worsening after the COVID-19 pandemic, as there was an increase in rates of psychological distress in general, including also the adolescence phase, where it presents a higher rate of young people with increased physical inactivity, anxiety levels, stress and depression, among other forms of suffering. Thus, as Basic Health Care (AB) is a gateway to the Psychosocial Care Network (RAPS), strengthening it becomes fundamental for comprehensive territorial-based care, as it represents the closest space to the user with your home. Therefore, it is essential to qualify the Family Health Teams (ESF), consolidate the link with the territory, carry out active searches with the Community Health Agent (ACS), carry out qualified listening/welcome, and provide matrix support for mental health teams, family participation and the empowerment of these young people. Therefore, the study aims to develop a practical guide aimed at health workers, proposing strategies for assisting adolescents in psychological distress within the scope of territorial PC care. This is an exploratory, descriptive and qualitative research. With the participation of 29 health professionals from the ESF working in the Basic Health Units (UBS) in the city of Parnamirim-RN. The representation of one UBS per territory was maintained, through a lottery-style draw, with at least one professional from each of the categories remaining, being selected through non-probability sampling called intentional sampling. As a technique for analyzing and presenting data, Content Analysis proposed by Bardin (2011) was chosen. Finally, with the help of the Canva platform, the “Practical guide for PC health professionals with territorial care strategies for teenagers from the Z and Alpha generations” was created, being of relevance to the municipality, as it presents care guidelines for adolescents, considering the local reality, alerting to the invisibility of the care of these young people in PHC, drawing the attention of municipal management to the weaknesses in the care of these young people and in the municipality's RAPS, strengthening the dialogue on the importance of professional qualification, multi-professionality, of intersectorality, family participation, listening, communication and care planning, for dignified assistance, which guarantees rights, social coexistence and comprehensive care in the territory.